Understanding Policing and Professional Practice - Sheldon, Barrie; Williams, Peter; Blockley, Tony (The Professional Policing Curriculum in Practice, 2022)
This book outlines the foundations for understanding modern policing. It is an essential introduction for all policing students and trainee police officers to the underpinning aspects of the profession, providing a clear understanding of how the police service is currently organised and how it fits into the wider criminal justice system. Students are encouraged to think critically and reflect upon core concepts such as policing by consent, police accountability, governance and professional standards, and it examines the challenges of policing an increasingly global, technical and diverse world.The Professional Policing Curriculum in Practice is a new series of books that match the requirements of the new pre-join policing qualifications. The texts reflect modern policing, are up-to-date and relevant, and grounded in practice. They reflect the challenges faced by new students, linking theory to real-life operational practice, while addressing critical thinking and other academic skills needed for degree-level study.